PENCIPTAAN BUKU ILUSTRASI PERMAINAN TRADISIONAL SEBAGAI UPAYA PELESTARIAN WARISAN BUDAYA LOKAL - Jafar, Aljuk (Jurnal Art Nouveau, 2014)
Abstract: The purpose of this research is to guide the creation of East Java illustrations of traditional games in an effort to preserve local cultural heritage by introducing traditional games of East Java. Traditional games currently almost marginalized and replaced with a modern game, with modern versatile tool anyway. This is mainly due to the rapid development of technologies that supports and produces various types of modern games it makes a lot of children in Indonesia did not recognized their ancient traditional games. Whereas traditional game is part of a culture that should be preserved and has a lot of positive values are good for childrens development. traditional childrens games have a close relationship with the development of intellectual, social, emotional, and personality of the child. The results showed that there are 4 kinds of games are very popular at that time, namely Engklek, Dakon, Patil Lele and Egrang is thought to have a high terapiutik value.Â Â Keywords: Traditional Game, Illustration Book, Introduction, History